Clinical implementation of molecular methods in detection of microorganisms from blood with a special focus on PCR electrospray ionization mass spectrometry. (4th May 2019) - Özenci, Volkan; Strålin, Kristoffer
ABSTRACT: Introduction : The ongoing improvement and development of state-of-the-art diagnostic methods indicate that we are in an era of revolution in clinical microbiological diagnosis of infectious diseases. Non-culture-based methods have the possibility to play a central role in delivering personalized microbiological diagnoses of severe infections. The PCR electrospray ionization mass spectrometry (PCR/ESI-MS) system is built on the principle of universal detection and specific identification. The performance studies using PCR/ESI-MS on whole blood samples, as well as our experiences, indicate that this method provides useful clinical information. These types of modern molecular methods deserve further development for broad implementation into clinical practices. Areas covered : The review describes briefly hitherto developed molecular assays in detection of microorganisms directly from whole blood and focuses on the clinical implementation of PCR/ESI-MS. Expert opinion : The detection of an extensive broad-spectrum of microorganisms directly from whole blood samples with a series of tests that are run automatically with a turn-around time of 8 h would be a desirable diagnostic tool for the clinical microbiology laboratories. We believe that the clinical experience with PCR-ESI MS may guide the development and establishment of similar state-of-the-art diagnostic technologies in medicine in the future.